The Role of Dividend Policy, Leverage, and Profitability in Influencing Profit Management in the Food and Beverage Sub-Sector on the IDX in 2021–2023 - Hendrayanti, Silvia; Fidyah Yuli Ernawati (International Journal of Economics, Business and Innovation Research, 2026)
Earnings management is a management effort to influence reported earnings. The purpose of this study is to determine the effect of dividend policy, leverage and profitability on earnings management in food and beverage subsector companies listed on the Indonesian Stock Exchange in 2021-2023. The population in this study were all food and beverage sub-sector companies Listed on the Indonesian Stock Exchange totalling 95. The sample in this study used purposive sampling so that 29 companies were obtained. The dependent variable in this study is earnings management, and the independent variables are dividend policy (XI), Leverage (X2) and Profitability (X3). The analysis method uses multiple linear regression analysis. Based on the results of the data analysis, it was concluded that dividend policy had no effect on earnings management with a significance value of 0.6885 0.05. Leverage affects earnings management with a significance value of 0.000 «0.05. Profitability affects earnings management with a significance value of 0.020 C0.05. The coefficient of determination value is 40.356. Suggestions that can be given to investors to pay attention to the leverage and profitability ratios because they affect profit management in the company, so that investment will be more profitable. For further researchers to take samples in other sectors so that results are obtained that better describe the condition of the company as a whole.